Maculopathy Development Mechanism in Choroid Tumor Localization Outside the Foveolar Zone - A. F. Brovkina; A. S. Stoyukhina; M. V. Budzinskaya; I. V. Musatkina (Oftalʹmologiâ)
The term “distant maculopathy” (DM) means the changes in the macular region, when the tumor is located at the distant from it. Purpоse: to study the peculiarities of the DM development, according to the tumor localization and present a possible mechanism of this symptom development. Patients and Methods. The study involved 53 patients with choroidal tumors localized outside the macular area, including 18 patients with neuroepithelial detachment (NED) in the macular area. In addition to the standard eye examination, all patients underwent EDI OCT. Results. In 1/3 cases of extrafoveolar located choroidal tumors according to OCT, exudative changes in the macular zone were revealed. In extrafoveral choroidal melanoma (CM), the biometric tumor parameters in patients with DM were slightly higher than the average in patients of this group, however, there was no correlation between the height of NED and tumor parameters. In extrafoveolar choroidal hemangioma (CH), a significant direct relationship between the height of the NED in the foveolar zone and the biometric parameters of the CH was found. In all cases, there was not choroidal elevation in the foveolar zone. The thickness and structure of the choroid in the subfoveolar zone in CM did not differ from the paired eye and the normal values. The thickness of the choroid in CH also did not differ from the paired eye, however, there was a slight expansion of the outer layers of the choroid (as in the paired eye) and an increase in its thickness compared with the norm. When a tumor is located above the macular zone, there is a “gravitational” mechanism for the development of DM, due to the spread of subretinal fluid (or blood) under the action of gravity. In case of juxtapapillar tumor localization, the appearance of DM is caused by microvascular disorders in the foveo-macular region of the retina and impaired axoplasmic current. In CM, the occurrence of NED may be associated with a retinal tension on the steeper side of the tumor. Conclusion. The development of distant maculopathy in CM is a sign of “active” tumor growth, in CH it develops later and depends on the size of the tumor. In identifying a high prevalent NED in the macular area, a careful examination of not only the central fundus zone, but also its peripheral parts is necessary.